(untitled) (MCIT: Proceedings of International scientific and practical conference, 2021)
A recent approach to learning Information and Coding Theory is suggested basing on power of modern computer science. Students willingly try to rediscover known and famous technologies by means of programming them. In order not to distract their attention, an ‘easy programming’ is suggested for what MATLAB seems to be the best tool. Collection of programs developed mutually by author and his students forms an ‘Information Theory Digital Laboratory’.